Effect of stellate ganglion block on the prevention of posttraumatic stress disorder in patients undergoing emergency ocular trauma surgery: protocol for a randomized, double-blind, placebo-controlled trial - Gao, Qi; Liu, Bin; Chen, Zhengjie; Li, Li; Li, Ning; Zhang, Gerong; Di, Shuo; Zhu, Yangzi; Zhu, Lei; Yu, Youjia (Frontiers in Medicine, 2025)
BackgroundPost-traumatic stress disorder (PTSD) is a prevalent and debilitating mental health condition that often develops after exposure to traumatic events. Stellate ganglion block (SGB) has been shown to alleviate PTSD symptoms, suggesting its potential as a preventive intervention, particularly in patients undergoing emergency ocular trauma surgery. However, the efficacy of SGB in preventing the onset of PTSD has not been clearly established.MethodsThis dual-center, randomized, double-blind, placebo-controlled trial will enroll 300 adult patients undergoing emergency ocular trauma surgery. Participants will be randomly assigned, in a 1:1 ratio and stratified by age (<65 or ≥65 years), to either the SGB group or the placebo group (n = 150 per group). Each participant will receive either an active right stellate ganglion block or a sham procedure administered 15 min prior to the induction of anesthesia. The primary outcome is the difference in the incidence of PTSD at 1 month after surgery. Secondary outcomes include the severity of PTSD, delayed-onset PTSD, the four core symptom clusters (intrusive re-experiencing, avoidance, negative alterations in cognition or mood, and hyperarousal and reactivity), the severity of dissociative symptoms, Beck Anxiety Inventory (BAI) scores at 24, 48, and 72 h postoperatively; Visual Analog Scale (VAS) sleep scores at 24, 48, and 72 h postoperatively; Numerical Rating Scale (NRS) pain scores at 24, 48, and 72 h postoperatively; Heart Rate Variability (HRV) measured intraoperatively and at 24 and 48 h postoperatively; recovery time; extubation time; Richmond Agitation-Sedation Scale (RASS) scores; and length of hospital stay. Safety outcomes will include neck pain, dizziness, tinnitus, respiratory depression, anaphylaxis, sinus bradycardia (defined as heart rate <50 beats/min), hematoma formation, infection, severe arrhythmia, pneumothorax, and complications related to general or spinal anesthesia. All data will be analyzed using a modified intention-to-treat (mITT) approach.DiscussionThis study aims to evaluate the efficacy and safety of SGB for the prevention of PTSD in patients undergoing emergency ocular trauma surgery.Clinical trial registrationChiCTR2500102717, www.chictr.org.cn/showproj.html?proj=270046.